2019
DOI: 10.1161/jaha.119.011922
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Circulating Glycine Levels and Risk of Coronary Artery Disease

Abstract: Background Recent studies have revealed sexually dimorphic associations between the carbamoyl‐phosphate synthase 1 locus, intermediates of the metabolic pathway leading from choline to urea, and risk of coronary artery disease ( CAD ) in women. Based on evidence from the literature, the atheroprotective association with carbamoyl‐phosphate synthase 1 could be mediated by the strong genetic effect of this locus on increased circulating glycine levels. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…Besides, since ABO antigens are also expressed on various other tissues including platelets and the vascular endothelium 20 , it could be speculated that the ABO locus may modulate VTE risk via VWF independent mechanisms. Such hypothesis is supported by several studies reporting the association of the ABO locus with different cardiovascular endophenotypes such as intercellular adhesion molecule-1 (ICAM-1), P-selectin and E-selectin [21][22][23][24][25] . Finally, the observation that plasma AGT activity can vary by a factor 1 to 3 in individuals of the same A1 blood 10 group strongly suggests that the variability in plasma AGT activity cannot be attributable only to ABO blood groups, emphasizing the need for a better assessment of the role of GTs in relation to VTE risk.…”
Section: Introductionmentioning
confidence: 77%
“…Besides, since ABO antigens are also expressed on various other tissues including platelets and the vascular endothelium 20 , it could be speculated that the ABO locus may modulate VTE risk via VWF independent mechanisms. Such hypothesis is supported by several studies reporting the association of the ABO locus with different cardiovascular endophenotypes such as intercellular adhesion molecule-1 (ICAM-1), P-selectin and E-selectin [21][22][23][24][25] . Finally, the observation that plasma AGT activity can vary by a factor 1 to 3 in individuals of the same A1 blood 10 group strongly suggests that the variability in plasma AGT activity cannot be attributable only to ABO blood groups, emphasizing the need for a better assessment of the role of GTs in relation to VTE risk.…”
Section: Introductionmentioning
confidence: 77%
“…Association between the SNPs rs10206976 and rs12613336 in the CPS1 gene were also pinpointed in a genome-wide association study (GWAS) [120], which suggested that individuals with a genotype leading to higher expression of CPS1 have lower levels of circulating glycine, and the opposite also holds true. Recently, meta-analysis of GWAS in 30,118 individuals of European ancestry showed four significant loci associated with circulating glycine levels [121]: two loci at the glycine cleavage system (GCS) subunits, protein P (SNP rs71503800 at GLDC , glycine decarboxylase) and protein H (SNP rs11860711 at GCSH ); and two novel loci at enzymes involved in serine metabolism SNP rs478093 in PHGDH (phosphoglycerate dehydrogenase) and SNP rs6955423 in PSPH (phosphoserine phosphatase). In addition, GWAS revealed an association between the levels of betaine and the SNPs s499368 in the SLC6A12 gene (which codes for a betaine transporter) and rs17823642 near the BHMT gene [119], and between the levels of dimethylglycine and the SNP rs2431332 at the DMGDH locus (coding for dimethylglycine dehydrogenase) [84].…”
Section: Potential Causes Of Decreased Glycine Availabilitymentioning
confidence: 99%
“…Besides, since ABO antigens are also expressed on various other tissues including platelets and the vascular endothelium 20 , it could be speculated that the ABO locus may modulate VT risk via VWF independent mechanisms. Such hypothesis is supported by several studies reporting the association of the ABO locus with different cardiovascular endophenotypes such as intercellular adhesion molecule-1 (ICAM-1), P-selectin and E-selectin [21][22][23][24][25] . Finally, the observation that plasma AGT activity can vary by a factor 1 to 3 in individuals of the same A1 blood 10 group strongly suggests that the variability in plasma AGT activity cannot be attributable only to ABO blood groups, emphasizing the need for a better assessment of the role of GTs in relation to VT risk.…”
Section: Introductionmentioning
confidence: 77%